Expression of hypoxia-inducible factor-1α predicts benefit from hypoxia modification in invasive bladder cancer - Hunter, B A (Nature Publishing Group, 2014)
BACKGROUND: The addition of carbogen and nicotinamide (CON) to radiotherapy (RT) improves overall survival in invasive bladder cancer. We explored whether expression of the hypoxia marker hypoxia-inducible factor-1α (HIF-1α) alone or in combination with other markers predicted benefit from CON. METHODS: A retrospective study was carried out using material from patients with high-grade invasive bladder carcinoma enrolled in the BCON phase III trial of RT alone or with CON (RT+CON). HIF-1α expression was studied in 137 tumours using tissue microarrays and immunohistochemistry. Data were available from other studies for carbonic anhydrase IX and glucose transporter 1 protein and gene expression and tumour necrosis. RESULTS: Patients with high HIF-1α expression had improved 5-year local relapse-free survival with RT+CON (47%) compared with RT alone (21% hazard ratio (HR) 0.48, 95% CI 0.26–0.8, P=0.02), no benefit was seen with low HIF-1α expression (HR 0.81, 95% CI 0.43–1.50, P=0.5). Combinations of markers including necrosis also predicted benefit but did not improve on prediction using necrosis alone. CONCLUSIONS: HIF-1α may be used to predict benefit from CON in patients with bladder cancer but does not improve on use of necrosis.